Discovery Learning Based on Local Potential Ternate Island: Strategies for Enhancing 21st Century Skills and Scientific Process of Multiethnic Students - Ade Haerullah; Jailan Sahil; Said Hasan; Arini Z. N.; Iswdi M. Ahmad; Jassia I. Pagala (UNIVERSITAS KHAIRUN, 2025)
This research aims to test the effectiveness of the local potential-based Discovery Learning model on improving 21st-century skills and students' understanding of the science process in seventh-grade students at Madrasah Tsanawiyah (MTs) Sahabat Cendikia Kota Ternate, who come from diverse cultural backgrounds. The research method uses a quasi-experimental design with a pretest-posttest control group, involving 40 students from classes VIIA and VIIB as samples. The instruments used were 21st-century skills tests and tests of the science process understanding of multiracial students. Inferential statistical analysis shows a significant effect (p<0.05) of the implementation of local potential-based Discovery Learning on improving the 21st-century skills of multiracial students (p=0.013) and the understanding of the science process of multiracial students (p=0.000). This can be interpreted that the use of Discovery Learning based on local potential is effective in developing both aspects. Additionally, the results of this study reveal how multi-ethnic students with different learning styles can achieve the same learning goals and appreciate diversity during and after using Discovery Learning based on the local potential of Ternate Island.